A Good Enough Reason: Addiction, Agency and Criminal Responsibility - Morse, Stephen J. (Inquiry, 2013)
The article begins by contrasting medical and moral views of addiction and how such views influence responsibility and policy analysis. It suggests that since addiction always involves action and action can always be morally evaluated, we must independently decide whether addicts do not meet responsibility criteria rather than begging the question and deciding by the label of ‘disease’ or ‘moral weakness’. It then turns to the criteria for criminal responsibility and shows that the criteria for criminal responsibility, like the criteria for addiction, are all folk psychological. Therefore, any scientific information about addiction must be ‘translated’ into the law’s folk psychological criteria. Distractions about responsibility are then quickly canvassed. Then it addresses the direct relation between addiction and criminal responsibility. It argues that most addicts retain sufficient rational and control capacities at the relevant times to be held responsible, especially for crimes that are not part of the definition of addiction itself. It suggests that there is good reason to excuse or mitigate addicts for the crimes of purchase and possession for personal use. It concludes by briefly considering what contemporary science can contribute to our understanding of addiction and agency